2006
DOI: 10.2209/tdcpublication.47.157
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Prolonged Breast- or Bottle-feeding on Dental Caries in Japanese Children

Abstract: The aim of this investigation was to study the effects of prolonged breast-or bottlefeeding on dental caries in Japanese infants. This longitudinal study was conducted by means of a questionnaire and clinical examination of 592 children at 18 months, 2 years and 3 years of age. The children were divided into three groups: 1) children still being breast-fed at 18 months of age (n‫;)24ס‬ 2) children still being bottle-fed at 18 months of age (n‫;)54ס‬ and 3) children weaned off of breast-or bottle-feeding and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
5
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 9 publications
2
50
5
5
Order By: Relevance
“…Other studies demonstrating the association between breastfeeding over 18 months and increased caries risk did not adjust for confounders [Yonezu et al, 2006;Prakasha Shrutha et al, 2013;Nobile et al, 2014]. Our analysis, adjusted for confounders, did not observe an association between prolonged full or any breastfeeding for >12 months and increased caries risk ( tables 4 , 5 ).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Other studies demonstrating the association between breastfeeding over 18 months and increased caries risk did not adjust for confounders [Yonezu et al, 2006;Prakasha Shrutha et al, 2013;Nobile et al, 2014]. Our analysis, adjusted for confounders, did not observe an association between prolonged full or any breastfeeding for >12 months and increased caries risk ( tables 4 , 5 ).…”
Section: Discussioncontrasting
confidence: 54%
“…An increased risk of dental caries associated with prolonged breastfeeding has been reported in several studies [Yonezu et al, 2006;Saraiva et al, 2007;Feldens et al, 2012;Prakasha Shrutha et al, 2013;Chaffee et al, 2014;Hong et al, 2014a;Nobile et al, 2014;Jain et al, 2015;Kato et al, 2015]. Compared to cow's milk, human milk presents more cariogenic properties responsible for dental caries, because it contains more carbohydrates but less calcium, phosphorus, and protein [Erickson and Mazhari, 1999;Bowen and Lawrence, 2005].…”
mentioning
confidence: 99%
“…We also found that children breast-fed at 18 months of age were several times more likely to have dental caries at 2 years of age than prolonged bottle-fed children 20) . However, this study did not answer the question of why prolonged breast-feeding was correlated with more dental caries.…”
Section: Introductionsupporting
confidence: 54%
“…On the other hand, a recent animal study 2) has suggested that high frequency exposure to human breast milk is more cariogenic than that to bovine milk, probably because human breast milk contains a higher concentration of lactose. The results of an earlier study by our group 21) showed that children who continued to breastfeed at the 14) . Earlier study by our group found that children who developed caries before 18 months of age exhibited high caries progression up to 3 years of age 19,20) .…”
Section: Discussionmentioning
confidence: 86%